Sostenibilidad ambiental: Gestión de residuos odontológicos en el Servicio Público - Mendes de Paula Gomes, Adrielle [UNESP]; Ísper Garbin, Artênio José [UNESP]; Moreira Arcieri, Renato [UNESP]; Saliba Rovida, Tânia Adas [UNESP]; Saliba Garbin, Cléa Adas [UNESP] (My University, 2017)
Introduction: medical waste is a serious problem for both society and the environment, and knowledge about its proper management is essential for the training of health care professionals. Objective: evaluate knowledge among dental professionals working in Basic Health Units from municipalities in northeast Sao Paulo, Brazil, about proper management of medical waste. Methods: the data collection tool used was a semi-structured questionnaire completed during visits to the health centers, aimed at verifying the adequacy of dental waste management. A descriptive analysis was performed. Additionally, chi-square and Fisher’s exact tests were applied to determine the association between waste disposal, and knowledge and information about the subject, using a significance level of 1 %. Analyses were conducted on BioEstat 5.0. Results: of the total professionals (n= 74), most (97.3 %) stated not knowing which are the medical wastes, and all believed that they may be harmful to health. However, 41.9 % did not provide a correct answer about disposal of infected gloves and suction devices, and 20.3 % about sharps disposal. With respect to information about the subject, 40.5 % did not obtain it. Conclusions: knowledge about proper disposal of medical waste is still deficient among these professionals, pointing to the importance of professional training and of proposing forms of proper management of medical waste.
Sustentabilidade ambiental: Gerenciamento de resíduos odontológicos no Serviço Público
Environmental sustainability: Dental waste management in the public service
Keywords: Brazil; Dental waste; Health legislation; Waste management